Comprehensive dataset on the physicochemical characteristics of agrowastes digestates from anaerobic digestionData.gouv.fr - Lucille Caradec; Aurélia Michaud; Mariana Moreira; Ivan Desneulin; Sylvaine Berger; Dominique Patureau; Sabine Houot; Florent Levavasseur; Antoine Savoie; Julie Jimenez (Data in Brief)
The established database represents one of the largest and most diverse collections of digestates compositions, with a total of 806 digestates derived from two main collections: (i) 608 digestates from French agricultural anaerobic digestion (AD) plants, which include detailed physicochemical characterization, trace metal elements and organic contaminants concentrations, and potential C and N mineralization during soil incubation in controlled conditions as agronomic indicators, and (ii) 198 digestates collected from an international literature review, with physicochemical characterization and some trace metal elements concentrations. An additional dataset of process metadata was also set-up, including feedstock compositions, operational conditions and post-treatments descriptions. A preliminary description of both collections is provided using descriptive statistics. This dataset can help to better understand the variability in digestates quality based on feedstock compositions, operational conditions and post-treatments, thereby improving their agronomic benefits.